Systematics of the genus Maietta Alexander with description of three new species (Diptera: Tipulomorpha: Limoniidae) - Santos, Daubian; Santos, Rodrigo Dos Reis; Ribeiro, Guilherme Cunha (Zootaxa, 2019)
The Neotropical genus Maietta Alexander (Diptera: Limoniidae), endemic to Southern South America (Chile), is revised. Three new species, M. dextra sp. n., M. edwardsi sp. n. and M. sinistra sp. n., are described and illustrated. An identification key is provided for all species. The phylogenetic relationships of the species are investigated in a cladistic analysis, resulting in one single most parsimonious cladogram with the topology ((M. squamigera + M. dextra sp. n.) (M. edwardsi sp. n. (M. trimedia + M. sinistra sp. n.))).